Applied structural and mechanical vibrations : theory and methods - Gatti, Paolo L., 1959- (CRC Press, Taylor & Francis Group, 2014)
The second edition of Applied Structural and Mechanical Vibrations: Theory and Methods continues the first edition's dual focus on the mathematical theory and the practical aspects of engineering vibrations measurement and analysis. This book emphasises the physical concepts, brings together theory and practice, and includes a number of worked-out examples of varying difficulty and an extensive list of references. What's New in the Second Edition:Adds new material on response spectraIncludes revised chapters on modal analysis and on.